Transformasi Pola Hidup Pekerja Migran Indonesia (PMI) di Lombok Timur Sebelum dan Setelah Keberangkatan ke Negara Tujuan - Syafarina, Luckia; Amini, Lulu; Ananta, Maodia; Nisa, Mayla Padiatun; Wijayanti, Ika (CV. Kurnia Grup, 2025)
This study examines the lifestyle changes of Indonesian Migrant Workers (PMI) in East Lombok Regency before and after working abroad. Using a qualitative approach and a case study design, data were collected through interviews and observations with five informants. The findings indicate that unstable economic conditions are the main reason PMIs decide to work overseas. Before departure, they generally worked in the informal sector with incomes sufficient only for basic needs. After working abroad, there was a significant economic improvement, enabling PMIs to save, purchase assets such as land or houses, and meet tertiary needs. Although their lifestyle has not drastically changed, PMIs feel more capable of planning a better future. The study also reveals that communication technology helps maintain relationships with family members back home. These findings provide insights into the dynamics of PMIs’ lives, particularly regarding their economic, social, and psychological well-being.